2018
DOI: 10.1002/cphc.201800119
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Quantum Kinetics in Ion Traps: State‐changing Collisions for OH+() Ions with He as a Buffer Gas

Abstract: We present quantum scattering calculations for rotational state‐changing cross sections and rates, up to about 50 K of ion translational temperatures, for the OH+ molecular ion in collision with He atoms as the buffer gas in the trap. The results are obtained both by using the correct spin‐rotation coupling of angular momenta and also within a recoupling scheme that treats the molecular target as a pseudo‐(1Σ+ ) state, and then compares our findings with similar data for the OH−(1Σ+ ) molecular partner under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
(58 reference statements)
4
14
0
Order By: Relevance
“…In practice, we found that we obtained converged inelastic cross sections by keeping λ max =18 in our potential expansion. The B 0 value for the MgH + rotor was taken to be 6.3870 cm −1 [28,29]. It is worth noting here that the present calculations cover a range of energies/temperatures which is much higher than that studied earlier by us on the present system [19,20].…”
Section: Computing the State-changing Collision Cross Sectionsmentioning
confidence: 69%
See 1 more Smart Citation
“…In practice, we found that we obtained converged inelastic cross sections by keeping λ max =18 in our potential expansion. The B 0 value for the MgH + rotor was taken to be 6.3870 cm −1 [28,29]. It is worth noting here that the present calculations cover a range of energies/temperatures which is much higher than that studied earlier by us on the present system [19,20].…”
Section: Computing the State-changing Collision Cross Sectionsmentioning
confidence: 69%
“…the average elapsed time required to reach the rotational-to-translational temperatures,is well below 1 s, being around 0.50 s at the lower T values and only reducing to 0.30 s at the highest experimental thermal temperatures. Such values are once more indicative of the collisional efficiency of the rotational cooling processes for MgH + , since similar calculations for the OH + ( 2 Σ) cation [29] indicated a τ value which was a factor of two larger over the same range of temperatures.…”
Section: Modeling the Cooling Kinetics In The Trapmentioning
confidence: 77%
“…It is therefore of direct interest when modelling possible operating conditions in the traps to know the size and temperature dependence of the collisioninduced state-changing processes for the molecular anion under study as the buffer gas selected is replaced by another, to test a broader range of operating conditions. In our previous work [11][12][13][14] we have examined a variety of small molecular anions and discussed the relative importance of their inelastic collision rate constants involving rotational states at different trap temperatures. Recent experimental work in our group has also been directed to photo-detachment studies of the CN À anion with He as the buffer gas of choice.…”
Section: Introductionmentioning
confidence: 99%
“…that associated with the trapping of the present cation under the much denser conditions of a cold ion trap where the He partner plays the role of the buffer gas. We have studied such processes many times in a variety of small molecular cations, so we shall not repeat the general discussion here but simply refer to those earlier publications [61][62][63][64] , while only a brief outline of the theory will be given below. We already know, in fact, that given the information we have obtained from the calculations , we are now in a position to try and follow the microscopic evolution of the cation's rotational state populations in a cold ion trap environment by setting up the corresponding rate equations describing such evolution, induced by collisional energy transfers with the uploaded He gas, as described in various of our earlier studies 65 :…”
Section: Rotational Relaxation Kinetics In Ion Trapsmentioning
confidence: 99%